Dimensions and level of resilience in university students, during the COVID-19 pandemic - Cruz Covarrubias, Lucila Patricia; Aguilar Pérez, Pedro; Aguilar Cruz, Pedro Daniel (EDU REVIEW. International Education and Learning Review / Revista Internacional de Educación y Aprendizaje, 2023)
The objective of the study was to assess the levels of resilience in university students. The design was quantitative, descriptive of an exploratory nature, based on the questionnaire of Resilience, Strength and Personal Security, the sample consisted of 469 students. The results show that a favorable percentage of students is highly resilient in the six factors studied. There are also some statistically significant differences in factors, according to sex. In conclusion, students with a high level of resilience have greater skills and resources to face adverse situations, such as the pandemic, both academically and personally.